Biomechanical analysis of stair ascent in persons with Chopart amputation. (June 2020) - Kaib, T; Schäfer, J; Block, J; Heitzmann, DWW; Putz, C; Alimusaj, M; Wolf, SI
Background: Compared to walking on level ground, ascending stairs requires a large range of motion not only of the hip and knee joint, but also of the ankle joint. The prosthesis often worn by persons with partial foot amputation largely prevents the ankle motion needed during stair ascent. Objectives: Aim of this study was to assess subjects with a Chopart amputation utilizing a clamshell device during stair ascent to identify potential biomechanical deficits. Study design: Cross-sectional study with reference group. Methods: Six subjects with unilateral Chopart amputation and 17 unimpaired subjects underwent three-dimensional motion analysis while ascending stairs in a step-over-step manner. Results: During weight acceptance, the involved side showed increased external hip-flexing and reduced knee-flexing moments and the sound side a higher ankle power than in the control group. The sound side showed higher external knee-flexing, dorsi-flexing, and hip-adducting moments than the controls during weight acceptance. Conclusion: The mechanism observed on the involved side differs from that in controls, but is comparable to the mechanisms used by subjects with transtibial amputation reported in the literature. However, compensatory movements on the sound side take place at the ankle and knee joint, differing from subjects with more proximal amputations. Clinical relevance: This study underpins the importance of adequate foot leverage and ankle function in cases of partial foot amputation, particularly in transfer situations such as stair ascent. If ankle range of motion is adequate, prosthetic/orthotic devices combining shank leverage with a hinged spring mechanism at the ankle may be promising.